Mengintip Prilaku Sombong Dalam Al-Qur’an - Hasiah, Hasiah (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
Arrogant and takabbur is behavior of rejecting the truth and belitting others with the greatest expression and the highest degree or rank of others. Arragant can be classified into three types, namely arrogant to Allah SWT. Arrogant to Apostle and Arrogant to fellow humans. There are several factors that can lead to arrogant attitudes, inducling know ledge, charity, worship, ancestry, beaty, good looks, power and strength and family. Arragont can result in punisment from Allah SWT